Dependence on Initial Conditions of Attainable Sets of Control Systems with p-Integrable Controls - Akyar, E. (Nonlinear Analysis: Modelling and Control, 2007)
Quasi-linear systems governed by p-integrable controls, for 1 < p < ∞ with constraint ‖u(·)‖p ≤ µ0 are considered. Dependence on initial conditions of attainable sets are studied.